Carbon‐Hybridized Hydroxides for Energy Conversion and Storage: Interface Chemistry and Manufacturing. Issue 14 (17th February 2023) - Xie, Yuanyang; Yu, Chang; Ni, Lin; Yu, Jinhe; Zhang, Yafang; Qiu, Jieshan
Abstract: Carbon‐hybridized hydroxides (CHHs) have been intensively investigated for uses in the energy conversion/storage fields. Nevertheless, the intrinsic structure–activity relationships between carbon and hydroxides within CHHs are still blurry, which hinders the fine modulation of CHHs in terms of practical applications to some degree. This review aims to figure out the intrinsic role of carbon materials in CHHs with a focus on the interface chemistry and the engineering strategy in‐between two components. The fundamental effects of the carbon materials in enhancing the charge/mass transfer kinetics are first analyzed, particularly the extra electron pathways for fast charge transfer and the anchoring sites for boosting the mass transfer. Subsequently, the surface‐guided/confined effects of carbon materials in CHHs to modify the morphology and tailor the hydroxides, and functional heterojunction for regulating the inner electronic structure are decoupled. The methods to efficiently construct a stable yet robust solid–solid heterointerface are summarized, including oxygen functional groups engrafting, topological defective sites construction and heteroatom incorporation to activate the inert carbon surface. The smart CHHs in some typical energy applications are demonstrated. Additionally, the methodologies that can reveal the hybridization electron configuration between two components are summed up. At last, the perspective and challenges faced by the CHHs for energy‐related applications are outlined. Abstract : The carbon‐hybridized hydroxides (CHHs) have unique superiorities in energy storage/conversion, in which the intrinsic roles of carbon at the heterogeneous interface are highlighted. The methods to construct a robust heterointerface in CHHs are summarized. The techniques to pinpoint the interface interaction and rehybridization electron configuration between carbon and hydroxides, and the future directions and perspective of the CHHs are outlined.